LITERATURE REVIEW : EFEKTIFITAS JAHE UNTUK MENGATASI EMESIS GRAVIDARUM PADA IBU HAMIL - Eko Riyanti, Nova Ari Pangesti, Sarifatun Naila (Jurnal Ilmiah Keperawatan, 2022)
Background:Emesisofgravidarum often occurs in pregnant women, where nausea is sometimes accompanied by vomiting less than 5 times. Nausea and vomiting are caused by an increase in HCG (Human Chorionic Gonadotropin) which can increase estrogen production. Nausea and vomiting that are not handled properly result in hyperemesis gravidarum which is a pathological effect of pregnancy. Nausea and vomiting can be overcome by complementary approaches, one of which is by giving ginger. Ginger containszingiberol, Vitamin A, flanderana, gingerol, curcumin, zingiberene essential oil, and bitter resin which are useful for blocking serotonin. Serotonin provides a sense of comfort in the stomach. Objective:To determine the effectiveness of ginger to reduce emesisof gravidarum. Methods: This study uses a literature review method by collecting and analyzing research articles that discuss the effectiveness of ginger to reduce emesisof gravidarum. The search for research articles is carried out using a database approach through Google Scholar. The selected research articles are research articles published from 2016 to 2020, full text, and indexed by ISSN. Results: Based on the five research articles that have been reviewed by the authors, it shows that ginger is most effective given 2 times a day for 4 days at a dose of 100 grams. Conclusion: Ginger is effective for reducing emesis of gravidarum in pregnancy which can be given in the form of wedang ginger and ginger extract.